Lean Work and Gender Inequalities: Manufacturing Consent at a Multinational Car Plant in Provincial Russia - Martin Krzywdzinski; Grzegorz Lechowski; Valentina Mählmeyer (Global Labour Journal, 2019)
How do local labour market structures, in tandem with workforce dispositions and attitudes, influence the way multinational companies localise their standardised work and production systems? This article investigates the conflict-ridden factory regime of a lean automotive plant in provincial Russia at which the management was able to secure a relatively high level of consent among its female workers but not among male workers. In order to explain this gendered pattern of worker consent, the plant-internal gender division of labour and two societal factors proved crucial: the gendered segmentation of the local labour market and the workers' cultural dispositions. At the same time, the analysis points to the transformative effect that the company's work and production system had on the local labour regime. The case study relies on a combination of quantitative survey data and qualitative interviews. It emphasises the need to reconnect the analysis of branch-plant factory regimes to a nuanced understanding of their embeddedness within local labour markets – also in the case of highly standardised work and production systems.
Keywords: 330; labour control regime; labour process; labour market; lean production; gender relations